Sports And Its Role On Adaptive Behaviour In Children With Special Needs - Habita , Attia; Serbout, Abed Elmalek (sports creativity, 2025)
The problem of children with special needs is not only in the field of education, but extend to the social domain, which is an important basis for their interaction with those around them, and this is reflected in the ability of these children to do tasks of daily life and exercise activities required in the community, because the school is the main source to gain the children's basic skills, their role is not limited only to provide preliminary information in reading and writing, but also to teach them how to reconcile to various positions inside and outside the school . This confirms the validity of the first hypothesis: therefore, we can say that the first hypothesis has been achieved. It is worth noting that training methods are one of the important means in the process of physical preparation and skills, especially when we have integrated them into a codified training program, as he pointed out. Therefore, we can say that the second hypothesis has been achieved for learners and players in developing the accuracy of handball scoring. Therefore, we can say that the second hypothesis has been achieved. There are no statistically significant differences between the average grades of pupils of institutes and the averages of pupils of intellectual education programs attached to ordinary schools in the sub-dimensions (receptive language, expressive language, reading and writing, rest and leisure time ). Therefore, we can say that the fourth hypothesis has been achieved.